Перспективи насінництва Picea omorica Purk. у Правобережному Лісостепу України - Pokhylchenko, O.P.; Petlovyj, I.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The article presents the results of Picea omorica Purk. introduction in Right-Bank of Forest-Steppe of Ukraine. There are the data about the season plant development, pollination, semination. The seed plantation is created.